Factors predictive of the efficacy of bezafibrate therapy in patients with primary sclerosing cholangitis. Issue 11 (17th January 2017) - Mizuno, Suguru; Isayama, Hiroyuki; Hirano, Kenji; Watanabe, Takeo; Takahara, Naminatsu; Kogure, Hirofumi; Matsubara, Saburo; Nakai, Yousuke; Tada, Minoru; Koike, Kazuhiko
Abstract : Aim: Primary sclerosing cholangitis (PSC) is a rare cholestatic disease. We previously reported the effects of bezafibrate on elevated hepatobiliary enzyme levels in patients with this disease both retrospectively and prospectively. In this study, we assessed factors predictive of bezafibrate efficacy. Methods: Twenty‐five patients with PSC, who underwent bezafibrate therapy (400 mg per day) from November 2006 to June 2015, were evaluated. Treatment was judged as being effective if the levels of all of the hepatobiliary enzymes decreased after 12 weeks. We investigated the patients' characteristics, disease history, concomitant medications, liver function, and liver stiffness. Results: The efficacy rate of bezafibrate was 60% (15/25 patients). The efficacy rate in patients graded as Child–Pugh class A was significantly higher (75% [15/20]) than that in patients graded as class B (0% [0/5], P  < 0.01). Non‐responders had higher liver stiffness values (18.0 vs. 8.8 kPa, P  = 0.19), and concomitantly used ursodeoxycholic acid more frequently (100% vs. 73%, P  = 0.12) than responders. Conclusions: We could not elucidate the factors predictive for bezafibrate efficacy for the treatment of PSC. However, bezafibrate was more effective for patients with preserved liver function (Child–Pugh class A) when it was prescribed before progression of liver fibrosis and failure of ursodeoxycholic acid therapy.